Deoxyribonucleic acid polymerase from the marine Pseudomonas sp. BAL-31. - Vicuña, R (1980)
A deoxyribonucleic acid (DNA)-dependent DNA polymerase (DNA nucleotidyltransferase) was purified 3,000-fold from the marine Pseuodomonas sp. BAL-31. The molecular weight of the native enzyme was estimated by glycerol gradient sedimentation to be 110,000. The enzyme migrated in sodium dodecyl sulfate-acrylamide gels as a single polypeptide with a molecular weight of 105,000. An absolute requirement for divalent cation was satisfied by Mg2+ or Mn2+ at concentrations of 1 mM. Monovalent cations at concentrations higher than 50 mM showed an inhibitory effect. The polymerase activity was resistant to N-ethylmaleimide and showed a wide pH optimum.